SELF-DISCLOSURE OF ADOLESCENTS AS THE MOST INFLUENTIAL FACTOR IN THE PROVISION OF REPRODUCTIVE HEALTH INFORMATION TO ADOLESCENTS - Kusumaningrum, Tanjung Anitasari Indah; Muhamad Taufik Hidayat; Anny Fauziyah; Rahmawati Setyaningrum; Tasya Aulianisa Hidayat; Mayang Widya Saputri (Universitas Airlangga, 2025)
Introduction: Adolescents with all their characteristics make them are vulnerable to reproductive health problems. Parents have the responsibility to provide reproductive health information to adolescents, but 52.67% of parents have not conveyed it. Aims: This study aimed to analyze the factors that most influence parent-to-adolescent communication regarding reproductive health. Methods: This type of research uses cross-sectional, which was conducted offline in 2022 in Jrakah Boyolali Village. The population of this study was 422 parents of teenagers, and the sample was 230 parents with adolescents aged 11-19 years. The sampling technique used was proportional random sampling. Data collection was carried out using validated instruments. The independent variables were communication patterns, joint activities, and adolescents’ self-disclosure, with parents' behavior in providing reproductive health information as the dependent variable. Data analysis was carried out with multiple logistic regression tests, with a significance level of 5%. Results: The study found that adolescent self-disclosure to their parents was the most influential factor in the provision of reproductive health information by parents to their adolescent children (OR=2.537 (95% CI OR:1.423-4.522). Parents with teenagers who are less open about telling their parents can increase the risk 2.537 times of not communicating reproductive health to teenagers. Adolescents' openness to their parents can increase the closeness between parents and adolescents, making it more possible to discuss reproductive health between the two. Conclusion: Parents need to learn communication techniques with teenagers so that teenagers are not embarrassed to discuss things.